2010
DOI: 10.1080/10177833.2010.11790634
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Attention Deficit Hyperactivity Disorder and Comorbid Disruptive Behavior Disorders Among School Age Children in Trabzon

Abstract: ÖZET:Trabzon ili ilkö¤retim ça¤› çocuklar›nda dikkat eksikli¤i hiperaktivite bozuklu¤u ve efllik eden y›k›c› davran›fl bozukluklar› yayg›nl›¤› Amaç: Bu çal›flman›n amac› Trabzon ilinde ilkö¤retim ça¤› çocuklar›nda Dikkat Eksikli¤i Hiperaktivite Bozuklu¤u'nun (DEHB) ve ona efllik eden Y›k›c› Davran›fl Bozukluklar›'n›n (YDB) yayg›nl›¤›n› incelemektir. Yöntem: Çal›flmada 6-12 yafl aral›¤›ndaki ilkokul ö¤rencilerinde (n=1126) DSM-IV tan› ölçütlerine göre DEHB ve YDB tan›lar›n›n konulmas› amac› ile Turgay'›n Çocuk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
3
18
2
1
Order By: Relevance
“…Moreover, ODD and ADHD prevalence rates were determined with the same methodology, but only ADHD prevalence rates were found to be high throughout the 4 waves. The ODD prevalence was found to be much less than the one detected in previous studies conducted in Turkey that was based on scale assessments [16,17]. These results may raise the question ''whether ADHD is more prevalent in Turkish children than in some other parts of the world?''…”
Section: Introductioncontrasting
confidence: 48%
“…Moreover, ODD and ADHD prevalence rates were determined with the same methodology, but only ADHD prevalence rates were found to be high throughout the 4 waves. The ODD prevalence was found to be much less than the one detected in previous studies conducted in Turkey that was based on scale assessments [16,17]. These results may raise the question ''whether ADHD is more prevalent in Turkish children than in some other parts of the world?''…”
Section: Introductioncontrasting
confidence: 48%
“…In Turkey, ADHD prevalence was not previously studied in extensive investigations, but two studies with diagnostic procedures including only parent and teacher scales reported the prevalence of ADHD in school age children between 6–12 and 6–15 years as 8.1% and 8.4 respectively [35,36]. It was interesting to find a higher ADHD prevalence in spite of the use of stricter methodology in our study.…”
Section: Discussionmentioning
confidence: 59%
“…However, the prevalence we found was higher than that of other prevalence studies carried out in Turkey in different years. A study conducted by Gul et al, 32 for instance, reported a prevalence of 8.6% and another one, reported by Ersan et al, 33 found a prevalence of 8.1%. Güler et al, 34 by contrast, reported a prevalence of 2.7-9.6% based on parent assessment and 2-10.1% based on teacher evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The global subtype studies reported that the combined and the inattentive types were the most common, 24,25 while two epidemiological studies from Turkey found that the hyperactive type was the most common. 32,33 These differences in the rates of various subtypes may stem from methodological variations as well as cultural discrepancies. More society-based studies are needed to interpret our results with respect to subtype distribution.…”
Section: Discussionmentioning
confidence: 99%